Phased array probe for the inspection of large steel forgings. Issue 1 (1st January 2021) - Dupont-Marillia, Frederic; Jahazi, Mohammad; Belanger, Pierre
Abstract: Reliable inspection of large steel forgings is a significant problem across multiple industries. When the dimensions of forgings are at least 1000 mm in each direction, ultrasonic phased array inspection becomes difficult because conventional probes are not designed to transmit and focus acoustic energy over such large distances. Using simulations and experiments, this article aims to discuss the possibilities and limitations of phased array imaging of large forged steel ingots. Simulations were used to design a transducer based on the reflected amplitude, as well as the lateral and axial resolutions of defects in a 1000 mm thick block. It was shown that when limiting the aperture to allow easy handling in an industrial inspection setting, the lateral resolution and the reflected amplitude were the main limitations. Increasing the element width maximizes the energy transmitted into the material, but it also moves elements away from each other, thus reducing the lateral resolution. Based on the simulations, an experimental phased array transducer was manufactured with eight elements of 9.25 × 22.5 mm. The probe was used to perform measurements and generate total focusing method images of three different at a depth of 370 mm in a 776 mm forged steel block.